To hell and back : my life in Johnny Thunders' heartbreakers, in the words of the last man standing /: my life in Johnny Thunders' heartbreakers, in the words of the last man standing. (2020) - Lure, Walter; (Writer on music), Thompson, Dave
No abstract available